Supercapacitor battery with high purity binder-free carbonaceous electrode
By using composite materials of high-purity carbon nanotubes and activated carbon in the active layer of supercapacitor batteries, the limitations of adhesives and carbon black in the prior art are solved, high energy and power density are achieved, and suitable for high temperature operation and direct surface mounting.
Patent Information
- Application Number
- CN202411732797.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-03
- Filing Date
- 2021-02-11
- Publication Date
- 2025-05-02
AI Technical Summary
The energy and power density of existing supercapacitors are limited by adhesive and carbon black, and the decomposition of adhesive at high temperatures limits the reflow soldering and direct surface mounting of the battery.
Using an active layer without adhesive, the conductivity and porosity of the electrode is improved by a composite of high-purity carbon nanotubes and activated carbon, reducing resistance and increasing energy and power density.
Supercapacitor batteries with high energy and power density are achieved, and due to the absence of adhesive, the batteries can operate stably at high temperatures and are suitable for direct surface mounting.
Smart Images

Figure CN119920634A_ABST
Abstract
Description
[0001] This application is a divisional application based on application number 202180022525.3, filed on February 11, 2021, and entitled “Supercapacitor battery with high-purity binder-free carbonaceous electrodes”. Technical Field
[0002] The present invention relates to a supercapacitor battery, in which at least one electrode comprises a current collector and an active layer, wherein the active layer comprises activated carbon and high-purity carbon nanotubes and does not contain a binder. Background Art
[0003] Supercapacitors are electrochemical storage devices that fill the gap between batteries and dielectric capacitors from an energy and power density perspective. Compared to batteries, supercapacitors can deliver higher power but store less energy; compared to capacitors, they store more energy but deliver less power.
[0004] The ability of an electrode to hold a charge is related to the porosity of its active layer, as high porosity results in high surface area. The ability of a supercapacitor to store charge is measured by its capacitance. The energy density of a supercapacitor is proportional to the capacitance and the square of the charge-voltage. The power density of a supercapacitor is inversely proportional to its internal resistance (also called equivalent series resistance) and is proportional to the square of the charge-voltage.
[0005] Activated carbon, because it is usually >1,000m 2 / g of high surface area, it is currently the most common material used for charge storage in capacitor electrodes. However, activated carbon is a poor electrical conductor and cannot be coated on a current collector foil without a binder. The binder is usually polymeric and insulating, such as polyvinylidene fluoride (PVDF). To increase conductivity, a conductive graphite material such as carbon black is added to the electrode. A mixture of activated carbon, carbon black and binder is dispersed in an organic solvent and coated on a current collector foil, usually aluminum or copper. The organic solvent is then removed by drying.
[0006] Conductive carbon black particles do not exhibit significant porosity and therefore do not contribute significantly to the storage of charge. Therefore, in terms of volumetric charge capacity, the carbon black particles and the binder are equivalent to dead volume. Therefore, the energy density of conventional supercapacitors is reduced by the inclusion of binders and carbon black.
[0007] The non-conductive binder increases the resistivity of the active layer of the electrode. Therefore, the power density of conventional supercapacitors is reduced by the inclusion of a binder. In addition, because the binder decomposes at high temperatures, its presence in supercapacitor electrodes limits the ability of supercapacitor cells to be reflow soldered for direct surface mounting onto printed circuit boards and electrical platforms. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 is a schematic diagram of the electrodes.
[0009] Figure 2 is an illustration of a detailed view of the active layer of the electrode.
[0010] Figure 3 is a schematic diagram of the bilateral electrodes.
[0011] Figure 4 is a flow chart showing a method of preparing an active layer of an electrode.
[0012] Figure 5 is a schematic diagram of an exemplary mixing device.
[0013] Figure 6 is a schematic diagram of a coating device with a slot die.
[0014] Figure 7 is a schematic diagram of a coating device equipped with a scraper.
[0015] Figure 8 is a schematic diagram of a supercapacitor cell.
[0016] Fig. 9 is a schematic diagram of a packaged supercapacitor cell.
[0017] Fig.10 is a photograph of the dried and calendered AC-CNT coating on the base layer on aluminum foil.
[0018] Fig.11 Nyquist plot of AC-CNT 80:20 wt % cell with PC electrolyte is shown.
[0019] Fig.12 Shown is the Nyquist plot of the AC-CNT 80:20 wt % cell with ACN electrolyte.
[0020] Fig.13 The changes in ESR and capacitance of AC-CNT 80:20wt% cells with PC / ACN electrolyte at a constant voltage of 2.7V / 2.5V and float charge at 70°C are shown with ≥98wt% pure CNTs and <98wt% pure CNTs.
[0021] Fig.14 Shown are the changes in ESR and capacitance of AC-CNT 80:20 wt % cells with PC / ACN electrolyte repeatedly cycled at 2.7 V / 2.5 V at 70 °C with ≥98 wt % pure CNTs and <98 wt % pure CNTs.
[0022] Fig.15Shown are the changes in ESR and capacitance of AC-CNT 80:20 wt % cells with PC-DMC electrolyte at 3 V and 70 °C.
[0023] Fig.16 shows the case with no bottom layer and with two types of bottom layers (one including sp 2 Nyquist plots of AC-CNT cells with ACN (top) and PC (bottom) electrolytes, with a preferred bottom layer of carbon. DETAILED DESCRIPTION
[0024] The present inventors have developed a supercapacitor electrode having an active layer including a composite material of activated carbon (AC) and high-purity carbon nanotubes (CNTs) and containing no binder.
[0025] References herein to "binders" are intended to convey the meaning of polymers, copolymers, and similar ultra-high molecular weight materials that are typically used to provide bonding to the carbon in the active layer of a supercapacitor electrode. Such materials are typically used as binders to promote cohesion between loosely assembled particulate materials (i.e., active filler materials that perform some useful function in a particular application). Examples of such binders include polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC), and polytetrafluoroethylene (PTFE).
[0026] The supercapacitor electrode of the present invention does not contain a binder in the active layer because it does not contribute to the charge storage capacity, so it is advantageous to replace it with a material (such as carbon nanotubes) that can be used to store charge and maintain the integrity of the electrode at the same time. In addition, the absence of a binder enables batteries containing supercapacitor electrodes of the present invention to be reflow soldered for direct surface mounting to printed circuit boards and electrical platforms.
[0027] A first aspect of the present invention relates to a supercapacitor cell having at least one electrode, the at least one electrode comprising a current collector and an active layer, wherein the active layer comprises activated carbon and carbon nanotubes having a purity of at least 95 wt%, and the active layer does not contain any binder. In general, a supercapacitor cell comprises two electrodes separated by a conductive solution comprising an electrolyte.
[0028] Carbon nanotubes are carbonaceous materials with high aspect ratios having significant surface area and low mass density. The CNTs used in the present invention are preferably single-walled carbon nanotubes (SWCNTs), but may also include double-walled carbon nanotubes (DWCNTs) and multi-walled carbon nanotubes (MWCNTs). Depending on their chirality, single-walled CNTs (SWCNTs) are either metallic (armchair) or semiconductor (zigzag or chiral). The SWCNTs in the present invention may be metal SWCNTs or semiconductor SWCNTs or preferably a mixture of metal and semiconductor SWCNTs. In addition, CNTs are purified to a degree where the content of detectable metals and other impurities is less than 5wt% and the Raman G / D integrated peak area ratio measured at a wavelength of 532nm is at least 20. In summary, this mixture of high-purity metal and semiconductor CNTs has a relatively high electrical conductivity.
[0029] AC is located within the network formed by CNTs. The binder-free active layer comprising AC and CNTs exhibits advantageous properties over an electrode active layer comprising activated carbon, carbon black and a binder. The inventors have further developed a process for preparing an aqueous dispersion of AC-CNTs by a high shear process without using a surfactant.
[0030] The electrode of the present invention includes an active AC-CNT layer without a binder. The preferred AC content in the active layer is 70 wt% to 90 wt%, more preferably 75 wt% to 85 wt%, and most preferably about 80 wt%. The preferred CNT content in the active layer is 10-30 wt%, and more preferably 15-25 wt%, and most preferably 20 wt%.
[0031] In one embodiment, the supercapacitor electrode of the present invention reduces or eliminates the amount of non-porous conductive carbon black particles in the active layer (electrode) of the supercapacitor to achieve high energy and power density. The active electrode material includes only porous and / or conductive materials to increase the charge storage capacity measured in units of volumetric capacitance and reduce the electrode resistance, which is the main contributing factor to the equivalent series resistance of the battery. For example, the active electrode material (active layer) includes less than 1wt% of carbon black or does not include any amount of carbon black, the carbon black does not exhibit significant porosity and does not contribute significantly to the storage of charge.
[0032] In another example, depending on specific target supercapacitor requirements, such as very low cell internal resistance, it may be desirable to include a minimal but sufficient amount of a conductive carbon black component in the electrode formulation, such as between 1 wt % and 6 wt % of the electrode.
[0033] In some embodiments, the electrode comprises an active AC-CNT layer having a thickness of 30 μm to 200 μm, more preferably 70 μm to 130 μm, and most preferably 90 μm to 110 μm. Reducing the thickness of the AC-CNT layer to less than 30 μm would unacceptably limit the total available capacitance of the assembled battery, while increasing the AC-CNT layer thickness to more than 200 μm would significantly limit the necessary facilitation of electrolyte ion diffusion into and out of the layer during charge and discharge operating cycles.
[0034] In some embodiments, the electrode includes a conductive bottom layer between the current collector and the AC-CNT active layer to reduce the interfacial resistance between the AC-CNT and the current collector. In some embodiments, the conductive bottom layer is a layer having at least 20%, preferably at least 40%, or at least 50%, or at least 60%, or at least 70% sp 2 The carbon layer has a hybrid carbon content and preferably has a thickness of 0.01 μm to 10 μm, more preferably 0.1 μm to 5 μm, and most preferably 0.5 μm to 3 μm. In some embodiments, the conductive bottom layer includes sp in the form of graphene, graphite, amorphous carbon, carbon black, fullerene, or any combination thereof. 2 Carbon, and does not include sp in the form of carbon nanotubes (CNTs) 2 carbon.
[0035] In some embodiments, stable, surfactant-free aqueous AC-CNT dispersions are prepared by a high shear process.
[0036] Figure 1 An electrode 100 for use in a supercapacitor of the present invention is shown. The electrode comprises a current collector 102, a bottom layer 104, and an active layer 106. For example, the active layer 106 acts as an energy storage medium by providing a surface interface with an electrolyte to form a double electrical layer. The bottom layer 104 is optional and can be omitted when the active layer 106 exhibits good adhesion and good electrical contact to the conductive layer 102.
[0037] In some embodiments, the active layer 106 may be in the range of 30 μm to 200 μm thick. The bottom layer 104 may have a thickness in the range of 0.01 μm to 10 μm.
[0038] Figure 2 An active layer 106 is shown that includes activated carbon 108 held together by a matrix 110 of carbon nanotubes (CNTs) 112 (eg, a mesh or network formed by the CNTs).
[0039] In some embodiments, for example, where the length of the CNTs is longer than the thickness of the active layer 106, the CNTs 112 forming the matrix 110 may be primarily parallel to the major surface of the active layer 106. It should be noted that while the CNTs 112 may form straight segments, in some embodiments, for example, where longer CNTs are used, some or all of the CNTs may instead have a curved or serpentine shape. For example, the CNTs 112 may bend and entangle between clumps of the activated carbon 108.
[0040] In some embodiments, the length of the CNTs 112 forming the matrix 110 may be in the range of 1 μm to 5,000 μm, or any sub-range thereof, such as 5 μm to 3000 μm, or 5 μm to 1000 μm, or 10 μm to 1000 μm.
[0041] In some embodiments, the purity of CNTs 112 forming matrix 110 is at least 95 wt%, preferably at least 97 wt%, and more preferably at least 98 wt%, and the Raman G / D integrated peak area ratio measured using a laser with a wavelength of 532 nm is at least 20, preferably at least 25, and more preferably at least 30.
[0042] The active layer of the present invention does not contain adhesives, such as polymer materials, binders, and the like.
[0043] The matrix 110 does not contain any binder, but holds the activated carbon 108 together and maintains the structural integrity of the active layer 106 without flaking, delamination, disintegration, etc.
[0044] The matrix 110 of carbon nanotubes provides a structural framework for the active layer 106, with the activated carbon 108 filling the spaces between the CNTs 112 of the matrix 110. In some embodiments, electrostatic forces (e.g., van der Waals forces) between the CNTs 112 and other carbonaceous materials 108 within the matrix 110 may provide substantially all of the bonding forces to maintain the structural integrity of the layer.
[0045] A second aspect of the invention relates to a stable aqueous dispersion of carbon, wherein the carbon comprises 70-90 wt % activated carbon and 10-30 wt % CNTs having a purity of at least 95 wt %; wherein the dispersion is surfactant-free; and is stable for at least 2 weeks, at least 1 month, at least 3 months, at least 6 months, at least 1 year or at least 2 years.
[0046] The aqueous dispersion refers to an aqueous solvent containing less than 10 wt %, or less than 5 wt %, or less than 1 wt %, or less than 0.1 wt % of an organic solvent, or an aqueous solvent without any organic solvent.
[0047] A stable dispersion is one in which no visible powders, particles, flakes or loose agglomerates precipitate out of the solvent or settle to the bottom of the mixture when no mechanical agitation is applied. In a stable dispersion, the carbon does not separate from the solvent and the carbon does not settle to the bottom of the container.
[0048] In some embodiments, an aqueous suspension of AC and CNT in water is formed by adding a mixture of AC and CNT powders to a container with water at a desired ratio in the range of (AC:CNT) 70:30 wt% to 90:10 wt%, more preferably 75:25 wt% to 85:15 wt%, or most preferably 80:20 wt%, while introducing mechanical energy into the mixture of AC, CNT and water, in the absence of a surfactant. The preferred concentration of carbonaceous materials (AC and CNT) in water is 20 to 40 g / L, more preferably 25 to 35 g / L, and most preferably 30 g / L.
[0049] In some embodiments, mechanical energy is added by stirring the mixture of AC, CNTs, and water with an impeller and / or by bath sonication before forming a suspension of AC and CNTs in water, ie, an aqueous suspension of AC and CNTs.
[0050] In some embodiments, a suspension of AC and CNTs in water is exposed to a subsequent high shear process to significantly disentangle the entangled CNT chains before forming a stable aqueous dispersion of carbon.
[0051] In some embodiments, the surface area of the AC is greater than 1,000 m 2 / g, preferably greater than 1,200m 2 / g, and more preferably greater than 1,500m 2 / g, and the BET surface area of CNT is greater than 400m 2 / g, preferably greater than 600m 2 / g, and more preferably greater than 800m 2 / g.
[0052] In some embodiments, the chemical purity of AC is greater than 95 wt%, preferably greater than 96 wt%, and more preferably greater than 98 wt%. The D50 particle size of AC, i.e., the median particle size where 50% of the particles are larger than a given size and 50% are smaller than a given size, is in a preferred range of 1 to 20 μm, more preferably 3 to 15 μm, and most preferably 5 to 7 μm.
[0053] In some embodiments, the chemical purity of the CNTs is at least 95 wt%, preferably at least 97 wt%, and more preferably at least 98 wt%, and the CNTs have a Raman G / D integrated peak area ratio measured using a laser with a wavelength of 532 nm of at least 20, preferably at least 25, and more preferably at least 30. Typical impurities are iron (Fe) from CNT synthesis catalysis and chlorine (Cl) from the CNT purification process. For example, a typical level of Fe impurities is about 1 wt%, a typical level of Cl impurities is 0.5 wt%, and the remaining impurities come from other elements, such as but not limited to nickel (Ni) and sulfur (S).
[0054] Furthermore, the amount of hydroxyl groups on the surface of the CNTs should be minimized, ie the CNTs should be free of hydroxyl groups (as can be assessed by Fourier transform infrared (FTIR) spectroscopy), since hydroxyl groups may react specifically with polar solvents such as acetonitrile (ACN).
[0055] The inventors have found that as the purity of CNTs increases to at least 95 wt%, the life of the supercapacitor cell is extended, as determined by an increase in cell resistance or a decrease in cell capacitance during a 1,000 hour float test at nominal cell voltage and temperature. The industry standard for a cell to pass such a test is to exhibit an increase in cell resistance of less than 100% and a decrease in cell capacitance of less than 30% after 1,000 hours of float. For example, a supercapacitor cell having at least 98 wt% purified CNTs free of hydroxyl groups in the AC-CNT active layer of the electrode and an acetonitrile electrolyte passed the life test at 2.5 V and 70 ° C. The same cell except with a propylene carbonate electrolyte passed the life test at 2.7 V and 70 ° C, and the same cell except with a polypropylene carbonate / dimethyl carbonate electrolyte passed the life test at 3.0 V and 70 ° C. Commercially available CNTs are typically less than 85 wt% pure; when they are used in electrodes for supercapacitors, the cell capacitance is reduced and cell failure is increased compared to the electrodes of the present invention used in supercapacitors.
[0056] The present inventors have discovered the unexpected result that an active layer comprising AC and CNTs in a desired ratio ranging from 70:30 wt % to 90:10 wt %, preferably 75:25 wt % to 85:15 wt %, and more preferably 80:20 wt % provides excellent battery performance (e.g., low resistance, high voltage performance, and high energy and power density) compared to a battery having an electrode comprising AC with carbon black and a binder.
[0057] In some embodiments, the matrix 110 of CNTs 112 forms an interconnected network of highly conductive paths for current to flow through the active layer 106. For example, in some embodiments, highly conductive junctions can occur at points where the CNTs 112 of the matrix 110 intersect each other, or where they are close enough to allow charge carriers to quantum tunnel from one CNT to the next. Although the CNTs 112 may constitute a relatively low mass fraction of the active layer (e.g., less than 25 wt%, 20 wt%, or 15 wt%), the interconnected network of highly conductive paths formed in the matrix 110 can provide long conductive paths to facilitate current flow within and through the active layer 106 (e.g., conductive paths on the order of the thickness of the active layer 106).
[0058] As used herein, the term “highly conductive path” should be understood as a path formed by interconnected CNTs 112 having an electrical conductivity higher than the electrical conductivity of the activated carbon material 108 .
[0059] Without being bound by theory, in some embodiments, the matrix 110 can be characterized as an electrically interconnected network of CNTs that exhibits connectivity above a percolation threshold. The percolation threshold is a mathematical concept related to percolation theory, which is the formation of long-range connectivity in a random system. Below the threshold, there is no so-called "giant" connected component of the order of the size of the system; while above the threshold, there is a giant component of the order of the size of the system. In the matrix 110 of the present invention comprising AC and CNTs in a specified ratio, the percolation threshold is exceeded based on the observed performance characteristics of the supercapacitor cell.
[0060] return Figure 1 In some embodiments, the conductive layer 102 may be made of a suitable conductive material, such as a metal foil. In some embodiments, the surface of the conductive layer 102 may be roughened, patterned, or otherwise textured, for example, to promote adhesion to the bottom layer 104 or the active layer 106, and good conductivity (i.e., low interface resistance) to the bottom layer 104 or the active layer 106. For example, in some embodiments, the conductive layer may be etched (e.g., mechanically or chemically).
[0061] In some embodiments, the conductive layer 102 may be aluminum, nickel, or copper foil.
[0062] In some embodiments, the thickness of the conductive layer 102 may be in a range of 1 μm to 1,000 μm or any sub-range thereof, such as 5 μm to 50 μm.
[0063] In some embodiments, bottom layer 104 may be omitted, such that active layer 106 is disposed directly on conductive layer 102 .
[0064] In some embodiments, the bottom layer 104 may mainly include sp2 For example, in some embodiments, the bottom layer 104 may be at least 20 wt %, preferably more than 40 wt %, more preferably more than 60 wt %, and most preferably more than 70 wt % sp 2 Carbon, and preferably has a thickness of 0.01 μm to 10 μm, more preferably 0.1 μm to 5 μm, and most preferably 0.5 μm to 3 μm.
[0065] In some embodiments, the bottom layer 104 contains less than 10 wt% carbon in the form of CNTs. Preferably, the bottom layer 104 contains less than 5 wt% carbon in the form of CNTs, or does not contain any carbon in the form of CNTs.
[0066] In some embodiments, the bottom layer 104 may be formed by physical vapor deposition (sputtering), ion beam deposition, chemical vapor deposition, plasma enhanced chemical vapor deposition, spray coating, screen printing, or formed from a slurry by coating.
[0067] In some embodiments, electrode 100 may be double-sided (see Figure 3 ), wherein the bottom layer 104 and the active layer 106 are formed on each of the two opposite major surfaces of the conductive layer 102. In some embodiments, the bottom layer 104 may be omitted on one or both sides of the double-sided electrode 100.
[0068] A third aspect of the present invention relates to a method for preparing a surfactant-free aqueous dispersion of activated carbon (AC) and carbon nanotubes (CNTs). The method comprises the following steps: mixing activated carbon and carbon nanotubes in a surfactant-free aqueous solution, wherein the carbon nanotubes have a purity of at least 95 wt % and are heated to at least 800,000 seconds. -1 A shear rate of 1000 s is used to apply high shear to the mixture.
[0069] The inventors have found that high purity CNTs (at least 95 wt%, or 97 wt%, or 99 wt%) significantly improve the stability of aqueous dispersions including activated carbon and CNTs. The inventors have also found that, without the use of surfactants, the stability of dispersions of AC (75-85 wt%) and CNTs (15-25 wt%) in water is significantly increased when the purity of the CNTs is at least 95 wt%, the Raman G / D integrated peak area ratio is at least 20, and the dispersion is exposed to a temperature having at least 800,000 seconds. -1 The high shear process with a shear rate of greater than 1,000,000 seconds is typically continued for at least two weeks, at least 1 month, at least 3 months, at least 6 months, at least 1 year, or at least 2 years. The shear rate is preferably greater than 1,000,000 seconds. -1 , and more preferably greater than 10,000,000 seconds -1 The maximum shear rate applied should not exceed 1,000,000,000 seconds-1 , and preferably should not exceed 100,000,000 seconds -1 , as shearing above this level may cause unacceptable damage to the carbon.
[0070] In general, water is the preferred solvent for preparing the active layer for environmental, economic and toxicological reasons, and is superior to organic solvents such as isopropyl alcohol (IPA), methanol, ethanol, N-methyl-2-pyrrolidone (NMP), dichloromethane (DCM), dimethyl sulfoxide (DMSO), dimethyl carbonate (DMC), propylene carbonate (PC), acetonitrile (ACN), etc. The stable aqueous dispersions of AC and CNTs provide considerable useful advantages over carbon dispersions in these organic solvents, which are harmful to the environment and human health and are more expensive in terms of raw materials and processing. However, IPA and NMP can also be used as solvents to prepare stable dispersions of AC and CNTs. In one embodiment, the stable dispersion of carbon in IPA includes 75-85wt% activated carbon and 15-25wt% CNTs in IPA, wherein the purity of the CNTs is at least 95wt%; the dispersion does not contain a surfactant; and is stable for at least two weeks.
[0071] In some embodiments, high shear rates can be achieved by passing the aqueous AC-CNT suspension through one or more channels at a high speed, such as 100 m / s, with diameters or cross-sectional dimensions between tens and hundreds of micrometers, wherein at least one diameter or cross-sectional dimension is preferably 200 μm or less, more preferably 150 μm or less, and most preferably 100 μm or less. For example, the aqueous AC-CNT suspension passes through a first channel with a cross-sectional dimension of 300 μm and a second channel with a cross-sectional dimension of 100 μm.
[0072] The high shear process is continued until a dispersion is obtained that exhibits a viscosity suitable for the coating process. The preferred viscosity of the dispersion in the temperature range of 20°C-80°C is in the range of 5,000 to 100,000 cP, more preferably in the range of 7,000 to 70,000 cP, and most preferably in the range of 10,000 to 50,000 cP.
[0073] refer to Figure 4, describes an exemplary embodiment of a method 200 for preparing an active layer 106 of an electrode 100. In step 201, AC and CNTs in a desired ratio ranging from 70:30 wt% to 90:10 wt%, preferably 75:25 wt% to 85:15 wt%, or more preferably 80:20 wt% are added to water. The preferred concentration of carbonaceous materials (AC and CNTs) in water is 20 to 40 g / L, more preferably 25 to 35 g / L, and most preferably 30 g / L. In an optional subsequent step 202, mechanical energy is added in the form of mixing or stirring by an impeller and / or by bath sonication for a period of time that ensures that AC and CNTs are well mixed in water to form an aqueous suspension of AC and CNTs. For example, the impeller can be operated at 500 rpm and a torque of 60 N·cm, while the bath sonicator can be operated at 37 Hz, 100 W, and 25° C. for about 1 hour.
[0074] No surfactant or dispersant is added in either step 201 or 202 to avoid the presence of impurities derived from these surfactants upon completion of method 200. In the absence of surfactant, the aqueous AC-CNT suspension typically remains in solution for between 1 and 6 hours without settling.
[0075] In step 203, the suspension of AC and CNTs in water is exposed to a high shear process in a high shear rotary mixer or by passing it through one or more channels with a diameter between tens and hundreds of microns in order to untangle the CNTs and form a stable dispersion. In the absence of surfactants, aqueous AC-CNT dispersions are typically stable for at least 2 weeks and up to 2 years.
[0076] In another embodiment of the method 200 for preparing the active layer 106 of the electrode 100, only CNTs are added to water in the first step 211. The preferred concentration of CNTs in water is between 4 and 8 g / L, more preferably between 5 and 7 g / L, or 6 g / L. In an optional subsequent step 212, mechanical energy is added in the form of mixing or stirring by an impeller and / or by bath sonication for a period of time sufficient to ensure that the CNTs are well mixed in water to form an aqueous suspension of CNTs. For example, the impeller is operated at 500 rpm and a torque of 60 N·cm, while the bath sonicator is operated at 37 Hz, 100 W and 25° C. for about 1 hour. No surfactant or dispersant is added in any of steps 211 or 212 to avoid the presence of impurities derived from these substances when the method 200 is completed. In the absence of a surfactant, the aqueous CNT suspension is typically kept in solution for between 1 and 6 hours without settling.
[0077] In step 213, the suspension of CNTs in water is exposed to a high shear process in a high shear rotary mixer or by passing it through one or more channels having a diameter between tens and hundreds of microns to untangle the CNTs and form a stable dispersion. In the absence of a surfactant, the aqueous CNT dispersion is typically stable for at least 2 weeks, at least 1 month, at least 3 months, at least 6 months, at least 1 year, or at least 2 years.
[0078] In step 214, AC is then added to the CNT dispersion at a desired AC to CNT ratio in the range of 70:30 wt% to 90:10 wt%, more preferably 75:25 wt% to 85:15 wt%, or most preferably 80:20 wt%. The preferred concentration of carbonaceous materials (AC and CNTs) in water is 20 to 40 g / L, more preferably 25 to 35 g / L, and most preferably 30 g / L. In step 215, mechanical energy is added in the form of mixing or stirring by an impeller and / or by bath sonication for a period of time that ensures that the AC and CNTs are well mixed in the water. For example, the impeller is operated at 500 rpm and a torque of 60 N·cm, while the bath sonicator is operated at 37 Hz, 100 W, and 25° C. for about 1 hour. In the absence of surfactants, the aqueous AC-CNT dispersion is typically stable for at least 2 weeks, at least 1 month, at least 3 months, at least 6 months, at least 1 year, or at least 2 years.
[0079] In step 221, the dispersion is applied to the base layer 104, or, if the base layer 104 is omitted, to the conductive layer 102 of the electrode 100, by a suitable process, such as doctor blade coating or slot die coating.
[0080] In step 222, the active layer is dried by exposing the active layer 102 to an elevated temperature for a specified duration, for example, 90°C for 40 minutes, by convection heating in air or in an inert gas, or infrared heating in the area to be dried.
[0081] In step 223, the electrode 100 coated with the active layer 102 is calendared under an applied set pressure (eg, between about 23,000 psi and 235,000 psi) to compress the active layer to its final thickness.
[0082] For example, an AC:CNT 80:20 wt% dispersion was applied at a knife distance of 4 mm, dried at 90°C and calendered at a pressure of 46,000 psi to produce an active layer with a final thickness of 100 μm.
[0083] For example, an AC:CNT 80:20 wt% dispersion was applied at a knife distance of 6 mm, dried at 90°C and calendered at a pressure of 46,000 psi to produce an active layer with a final thickness of 150 μm.
[0084] In a fourth aspect, the present invention relates to a method of coating a substrate such as a current collector or a current collector primed with a carbon primer, the method comprising: knife coating or slot die coating an aqueous dispersion onto the substrate, wherein the dispersion comprises activated carbon and carbon nanotubes, is free of any surfactant, and has a viscosity in the range of 5,000 to 100,000 cP, and the purity of the carbon nanotubes is at least 95 wt%.
[0085] Advantageously, in some embodiments, the method 200 for forming the active layer 106 may be implemented as a roll-to-roll process (eg, to allow for batch production of electrode sheets tens of meters or longer).
[0086] Figure 5 An exemplary apparatus 300 for preparing the active layer 106 of the electrode 100 is shown.
[0087] Apparatus 300 comprises container 301. In some embodiments, an aqueous AC-CNT suspension may be initially formed in container 301. In other embodiments, the mixture may be formed elsewhere and then transferred to container 301.
[0088] In some embodiments, the vessel 301 may contain an agitation mechanism, such as an impeller operating at a controlled speed or another device known in the art.
[0089] In some embodiments, container 301 may contain one or more devices for homogenization, such as a sonicator or other devices known in the art.
[0090] In some embodiments, the temperature of the vessel 301 may be controlled using, for example, one or more heating and / or cooling elements, such as an electric heater, a line for circulating chilled water, or any other such device known in the art.
[0091] The aqueous AC-CNT suspension in container 301 is passed through a flow line 302, such as a pipe or tubing, using a pump 303. Pump 303 can be of any suitable configuration, such as a peristaltic pump. A flow meter 304 can be provided to measure the rate at which the mixture flows through flow line 302. A filter 305 can be provided to filter the mixture flowing through flow line 302, for example to remove agglomerates of solid material having a size above a desired threshold.
[0092] In some embodiments, the aqueous AC-CNT suspension is passed through one or more channels 306 having diameters or cross-sectional dimensions ranging from tens to hundreds of microns, with at least one diameter or cross-sectional dimension preferably being 200 μm or less, more preferably 150 μm or less, and most preferably 100 μm or less. The CNTs in the aqueous AC-CNT mixture are untangled by exposure to high shear.
[0093] In some embodiments, a temperature control device 307 , such as a heat exchanger disposed in a sleeve disposed around the flow line 302 , is provided to control the temperature of the aqueous AC-CNT dispersion flowing through the flow line 302 .
[0094] In some embodiments, a valve 308 is provided that can be selectively controlled to direct a first portion of the AC-CNT aqueous dispersion through a return flow line 310 to be recycled back to the container 301 , while a second portion is output externally, for example, to the coating apparatus 400 .
[0095] In some embodiments, a sensor 309, such as a pressure sensor and / or a flow rate sensor, is provided to sense one or more aspects of the output portion of the dispersion.
[0096] In various embodiments, any or all of the elements of the apparatus 300 may be operably connected to one or more computing devices to provide automatic monitoring and / or control of the mixing apparatus 300 .
[0097] In various embodiments, coating apparatus 400 may be of any suitable type known in the art. Figure 6 An exemplary embodiment of a coating apparatus 400 having a slot die 401 is shown that distributes an aqueous AC-CNT dispersion received from a source such as apparatus 300 through a distribution channel 402 onto a substrate 403 (e.g., conductive layer 102, bare or coated with a base layer 104), which moves across rollers 404. Setting the height of the slot die above the substrate 403 on rollers 404 and controlling the flow rate and / or pressure of the dispersion in channel 402 allows control of the thickness and density of the applied coating. In some embodiments, channel 402 may contain one or more reservoirs to help ensure a constant flow of the aqueous AC-CNT dispersion, thereby providing a uniform coating during operation.
[0098] refer to Figure 7 In various embodiments, coating apparatus 500 is provided with a scraper 501 that smoothes a dispersion received from a source such as apparatus 300, which is applied by one or more applicators 502 (one shown) to a substrate 503 (e.g., conductive layer 102, either bare or coated with a base layer 104), which moves across rollers 504. The direction of travel of substrate 503 is indicated by an arrow. Setting the height of scraper 501 above substrate 503 on rollers 504 and controlling the flow rate and / or pressure of the AC-CNT dispersion through applicators 502 allows control of the thickness and density of the applied coating. Although a single scraper 501 is shown, multiple blades may be used, for example, with a first blade setting the rough thickness of the coating and a second blade located downstream of the first blade to provide fine smoothing of the coating.
[0099] Although a process for forming an AC-CNT electrode without the presence of carbon black (CB) has been described above, a small amount of CB, such as between about 1 and 6 wt%, may be added during step 201 or 214 of method 200 to reduce the overall equivalent series resistance (ESR) of the supercapacitor cell. For electrode formulations containing carbon black, the ratios of AC:CNT:CB are adjusted to x:yz:z wt%, respectively; that is, the amount of CNT is reduced by the amount of CB added. For example, one embodiment of the electrode formulation includes a ratio of 80:15:5 wt% AC:CNT:CB. Although the presence of a small amount of carbon black may reduce the battery ESR, since carbon black cannot store charge, the volumetric capacitance of the battery with AC-CNT-CB electrodes will be lower than that of a battery of the same design with AC-CNT electrodes.
[0100] Figure 8 An exemplary embodiment of a supercapacitor 600 is shown (Obreja, Physica E 40 (2008), 2596-2605).
[0101] The exemplary supercapacitor 600 cell is an electric double layer capacitor (EDLC). The EDLC comprises at least one pair of electrodes 603 and 604 (wherein electrode 603 may be referred to as a negative electrode and 604 may be referred to as a positive electrode, for reference purposes only herein) having a pore structure 607. When assembled into the supercapacitor 600, each of the electrodes 603 and 604 (each of which may be Figure 1 Electrodes 100 of the type shown in the figure exhibit a double layer of charge at the electrolyte interface. In some embodiments, multiple electrodes 603 and 604 are included. However, for the purpose of discussion, only one pair of electrodes 603 and 604 is shown. As a convention herein, at least one, but more typically both, of electrodes 603 and 604 include a binder-free, surfactant-free AC-CNT active layer having a pore structure 607 (e.g., Figure 1 1 and 10. The active layer 106 of the electrode 100 is shown.
[0102] Each of the electrodes 603 and 604 comprises a corresponding current collector 601 and 602 (also called a "charge collector"), which may be Figure 1 Conductive layer 102 of electrode 100 is shown. In some embodiments, electrodes 603 and 604 are separated by separator 605. Generally, separator 605 is a thin structure, porous, non-conductive material (usually a cellulose or polymer sheet) used to separate negative electrode 603 from positive electrode 604. Once assembled, electrodes 603 and 604 and separator 605 provide battery 600.
[0103] At least one form of electrolyte 606 that conducts electricity by ion transport is contained in the supercapacitor 600. The electrolyte is composed of a salt dissolved in an aqueous or organic solvent, or an ionic liquid, and the dissolved salt or ionic liquid dissociates into negative ions (anions) 609 and positive ions (cations) 611. The electrolyte 606 impregnates the porous separator 605 and the pore structure 607 in the active layer and fills the space within the electrodes 603 and 604.
[0104] In some embodiments, the electrolyte comprises about 1.8 M triethyl-methyl-ammonium tetrafluoroborate (TEMA-BF) dissolved in at least 99.9% pure, preferably at least 99.99% pure propylene carbonate (PC). 4 ).
[0105] In some embodiments, the electrolyte comprises 1 M tetraethylammonium tetrafluoroborate (TEA-BF) dissolved in at least 99.9% pure, preferably at least 99.99% pure, acetonitrile (ACN). 4 ).
[0106] In some embodiments, the electrolyte comprises 1 M tetraethylammonium tetrafluoroborate (TEA-BF) dissolved in at least 99.9% pure, preferably at least 99.99% pure, propionitrile (PN). 4 ).
[0107] In some embodiments, the electrolyte comprises 1.5 M 5-azaspiro[4.4]nonane-tetrafluoroborate (SPB-BF) dissolved in a mixture of at least 99.9% pure, preferably at least 99.99% pure PC and an aliphatic additive such as dimethyl carbonate (DMC). 4 ).
[0108] In some embodiments, the volume of the positive electrode and the negative electrode is substantially the same, as determined by their respective thicknesses and areas. For example, both electrodes may have a thickness of about 100 μm and an area of about 3 cm. 2 Since the radii of anions and cations in the electrolyte are different, for example, in BF 4 In the case of anions and TEA or TEMA cations, the anions may be smaller than the cations, so it may be advantageous for the negative and positive electrodes to have different volumes by varying the thickness or area of one relative to the other. For example, the capacitance of the positive electrode may be 10% greater than the capacitance of the negative electrode due to faster diffusion and lower desolvation energy of anions relative to cations. In this case, a negative electrode that is 10% larger in volume than the positive electrode, such as 10% thicker or 10% larger in area, is advantageous.
[0109] When a bias voltage is applied between the two electrodes, a positive charge layer 608 is formed at the exposed pore surface of one electrode and causes attraction of negative ions 609 from the electrolyte 606, and a negative charge layer 610 at the exposed pore surface of the other electrode causes attraction of positive ions 611 from the electrolyte 606. Thus, a double electric layer is formed at either inner electrode surface and a high capacitance value is achieved.
[0110] In some embodiments, the supercapacitor battery is formed by packaging the supercapacitor cell 600 into a hermetically sealed enclosure 900, either as a pouch cell with generally flat electrodes, or a cylindrical cell, or a prismatic cell with tightly wound electrodes.
[0111] refer to Fig. 9 , the battery is hermetically sealed by welding techniques known to those skilled in the art, such as using laser, ultrasonic or other welding techniques. In addition to providing robust physical protection for the battery 600, the housing 900 is configured with external contacts to provide electrical communication with corresponding terminals 901 and 902 within the housing 900. Each of the terminals 901 and 902, in turn, generally provides electrical access to the energy stored in the active layers of the electrodes 603 and 604, respectively, through electrical leads connected to the electrodes 603 and 604, respectively.
[0112] Supercapacitor cells are rated with a nominal capacitance expressed in farads (F) and a maximum operating voltage (V). Multiple supercapacitor cells 900 can be joined together to form a group by electrically connecting them in series, in parallel, or in a combination thereof. The series electrical connection of the cells will increase the maximum operating voltage while reducing the nominal capacitance of the couple. The parallel electrical connection of the cells will increase the nominal capacitance of the couple. For example, connecting two 1F / 2.5V cells in series will provide a 0.5F / 5V cell-couple. For example, connecting two 1F / 2.5V cells in parallel will provide a 2F / 2.5V cell-couple. For example, connecting two groups of two 1F / 2.5V cells in series and connecting the two groups in parallel will provide a 1F / 5V cell-couple.
[0113] Examples
[0114] Example 1 - Performance characteristics of supercapacitor cells with AC-CNT electrodes of various formulations containing purified CNTs
[0115] AC-CNT dispersion treatment
[0116] For a dispersion volume of 1 L, 24 grams of a BET surface area of about 1,900 m 2 / g of activated carbon powder and 6 grams of surface area of about 800m 2 / g and Raman G / D integrated peak area ratio> 30 ≥ 98wt% purified CNT powder was introduced into water and pre-mixed for 30 minutes by impeller mixing and bath ultrasonic treatment, followed by 300μm channel and 87μm channel connected in series for 3 times. The aqueous dispersion product is an AC-CNT (80:20wt%)-water dispersion with a concentration of 30g / L. The aqueous dispersion is stable for at least 2 weeks when placed at 20°C.
[0117] Doctor blade coating of AC-CNT onto Al current collector with carbon underlayer
[0118] The freshly prepared aqueous AC-CNT dispersion was doctor-bladed onto a substrate containing >50% sp 2 The carbon bottom layer was coated on a commercial Al current collector foil. The knife gap was set at around 4.0 mm to obtain a final coating thickness of 100 μm. A full platform length of about 30 cm was used for knife coating of the AC-CNT dispersion. Fig.10 An example of a large area AC-CNT coating made using a knife coater over the entire platform after drying is shown. The average time to dry one such coating using a dual heat gun was 35 minutes. The dried AC-CNT coating had good adhesion to the underlying carbon-primed Al current collector without showing signs of delamination. The large area AC-CNT coating was calendered using a pair of cover foils using a roller press at a pressure of 46,000 psi and a speed of 3 m / min, followed by vacuum oven drying at 200 °C for 16 hours.
[0119] Electrodes for pouch cell modules
[0120] Electrodes of size 15 mm x 20 mm were punched from various 100 μm thick AC-CNT coated aluminum strips for assembly into pouch cells. A 20 μm thick cellulose separator was incorporated into pouch cells filled with PC-based or ACN-based electrolytes. Twenty (20) EDLC pouch cells were assembled, ten (10) with 1.8 M TEA-BF 4 Ten (10) batteries with 1M TEMA-BF 4 ACN battery with salt electrolyte.
[0121] AC-CNT battery with PC electrolyte
[0122] from Fig.11In the cumulative plot of ten Nyquist characteristic curves of EDLC pouch cells containing AC-CNT 80:20 electrodes and PC-based electrolytes shown, it can be seen that the dispersion of ESR values between cells is relatively low. It is worth noting that there is no ESR semicircle artifact at high frequencies, indicating that the 100μm thick AC-CNT active layer has good adhesion to the Al current collector coated with carbon. Warburg diffusion artifacts at high to medium frequencies are characteristic of thick electrodes in PC solvents. The average cell ESR value at 1kHz frequency is 0.63±0.02Ω·cm 2 The average cell response time as measured by a 45 degree phase angle between the imaginary and real parts of the impedance was 5.0 seconds.
[0123] AC-CNT battery with ACN electrolyte
[0124] Fig.12 Nyquist curves of the corresponding EDLC pouch cells containing AC-CNT 80:20 electrodes and ACN-based electrolyte are shown. Similar to the PC-filled cells, there is no ESR semicircle artifact at high frequencies, indicating good adhesion of the 100 μm thick AC-CNT active layer to the primed Al current collector. Warburg diffusion artifacts at high to medium frequencies are still prevalent, however, its amplitude is significantly lower compared to the same electrode in PC solvent. The average cell ESR value at 1 kHz frequency is 0.23 ± 0.02 Ω 2 The average cell response time as measured by a 45 degree phase angle between the imaginary and real parts of the impedance was 1.4 seconds.
[0125] Table 1 summarizes the EDLC performance characteristics of cells with AC-CNT electrodes of various formulations.
[0126] Table 1
[0127]
[0128] Example 2 - Stability of Carbon Dispersion
[0129] Carbon dispersions were prepared from 100% carbon nanotubes (CNTs) or a mixture of 20 wt% CNTs and 80 wt% activated carbon in deionized water or isopropyl alcohol (IPA). CNTs with three different purity levels, about 85 wt%, about 97.5 wt%, and about 99 wt%, were used to prepare the dispersions. No surfactants or other components were added to the dispersions during the preparation process.
[0130] All dispersions were prepared by the following process: the carbon component and the solvent component (water or IPA) were first combined in a container, and then the components were mixed with an impeller mixer running at 500 rpm and 60 N·cm of torque, while ultrasonically treating in a bath at 37 Hz, 100 w and 25° C. for 1 hour. The resulting suspension was then subjected to high shear by passing the resulting suspension through two series channels with cross sections of 300 μm and 100 μm three times at a pressure of 25,000 psi. The resulting dispersion was collected in a glass jar and sealed. The dispersion in the jar was observed to observe visual signs of carbon separation from the solvent or carbon settling at the bottom of the container. The duration of stability was determined as the length of time that no such settling separation was visually observed in the jar.
[0131] As shown in Table 2, dispersions prepared with 85 wt% pure CNTs in water solvent, whether prepared with CNTs alone or as a mixture of AC and CNTs, showed poor stability. In contrast, dispersions prepared with 97 wt% or 99 wt% pure CNTs in water solvent, whether prepared with CNTs alone or as a mixture of AC and CNTs, showed excellent stability, with no separation or sedimentation observed after at least 6 months. For all CNT purity levels and compositions, dispersions prepared in IPA showed comparable stability to dispersions prepared using 97 wt% or 99 wt% pure CNTs in water.
[0132] Table 2
[0133] Carbon composition CNT purity (wt%) Carbon concentration (g / L) Solvents Duration of stability CNT 85 11 water 5 minutes CNT 97 11 water >6 months CNT 99 11 water >6 months 80AC: 20CNT 85 30 water 20 minutes 80AC: 20CNT 97 30 water >6 months 80AC: 20CNT 99 30 water >6 months CNT 85 11 IPA >6 months CNT 97 11 IPA >6 months CNT 99 11 IPA >6 months 80AC: 20CNT 85 15 IPA >6 months 80AC: 20CNT 97 15 IPA >6 months 80AC: 20CNT 99 15 IPA >6 months
[0134] Example 3 - Comparison of Lifetime Performance Data Between Supercapacitor Cells with AC-CNT Electrodes Containing Non-Purified CNTs and ≥98 wt% Purified CNTs
[0135] Aqueous dispersions of AC-CNTs with a purity of about 85 wt% or less of CNTs without surfactant were not stable because the CNTs settled out in a short time, typically in about an hour or less (see Example 2). Since suspensions of AC-CNTs with unpurified CNTs (e.g., CNTs with a purity of about 85 wt%) did not form stable dispersions in water using the described high shear process in the absence of surfactant, AC-CN suspensions were prepared in isopropyl alcohol (IPA) instead of water and exposed to the same high shear process.
[0136] Therefore, cells with AC-CNT active layers with high purity CNTs formed from water-based dispersions were compared with cells with AC-CNT active layers with unpurified CNTs formed from IPA-based dispersions. Cells with PC-based or ACN-based electrolytes were tested for 1,000 hours of float charge at constant voltage and 100,000 constant current charge-discharge cycles.
[0137] 1,000 hours float test at 70°C:
[0138] Float charging was performed by keeping the battery at a fixed voltage and a high temperature of 70°C. The battery with PC electrolyte was float charged at 2.7V, while the battery with ACN electrolyte was float charged at 2.5V. Fig.13 As shown, under the same test conditions, the battery ESR and capacitance changes of AC-CNT batteries with non-purified CNTs are significantly greater than those of AC-CNT batteries using ≥98wt% purified CNTs. The AC-CNT battery with non-purified CNTs (≤85wt% purity) and filled with an ACN-based electrolyte failed after 400 hours due to a doubling of its battery ESR (●). This battery also had the largest capacitance decay. At the end of the 1,000-hour float test, the AC-CNT battery using non-purified CNTs and filled with a PC-based electrolyte showed an 86% increase in ESR and a 22% decrease in capacitance ( ). In contrast, the two AC-CNT cells using ≥98 wt % purified CNTs performed significantly better than their AC-CNT (non-purified CNT) counterparts (☆ and ★).
[0139] 100k cycle test at 70℃
[0140] Cycling was performed by repeatedly charging to 2.7 V and discharging to 0.1 V for the battery with PC electrolyte and repeatedly charging to 2.5 V and discharging to 0.1 V for the battery with ACN electrolyte while keeping the battery at a high temperature of 70°C. The ESR and capacitance changes of the two types of AC-CNT batteries in PC (2.7 V) and ACN (2.5 V) during the cycle test are shown in Fig.14 AC-CNT batteries with non-purified CNTs in PC electrolyte ( ) showed similar cycling performance compared to AC-CNT cells with ≥98wt% purified CNTs in PC electrolyte (☆). However, when the filled electrolyte was ACN, the AC-CNT cell with non-purified CNTs failed only after 40k cycles, showing an ESR increase of 105% (●) and the corresponding highest capacitance drop. This is in stark contrast to the AC-CNT pouch cells with ≥98wt% purified CNTs filled with an ACN-based electrolyte, which passed the 100k cycle test, showing a cell ESR increase of <40% and a capacitance decay of <10% (★).
[0141] Table 3 summarizes the lifetime performance comparison between cells with AC-CNT electrodes containing non-purified (np) and purified (p) CNTs.
[0142] Table 3
[0143]
[0144] * p = purified (≥98 wt%); np = non-purified
[0145] Example 4 - Lifetime performance data of EDLC cells assembled with AC-CNT electrodes at high voltage
[0146] A limitation of EDLC cells filled with conventional organic-based electrolytes PC and ACN is that their maximum operating voltages are limited to 2.7 V and 2.5 V, respectively. Operating such cells for extended periods of time at voltages exceeding their maximum operating voltages can cause electrochemical decomposition of the electrolyte solvents and / or salts, leading to drastic and irreversible cell failure. The AC-CNT EDLC cells of the present invention are filled with a modified organic-based electrolyte consisting of a binary system of PC and an aliphatic additive dimethyl carbonate (DMC) and containing 1.5 M spiro salt 5-azaspiro[4.4]nonane-tetrafluoroborate (SPB-BF 4 ). The floating charge life performance of the AC-CNT battery combined with this binary electrolyte is shown in Figure 2 at 3V and 70°C. Fig.15 After biasing at 3 V for 1,000 hours, the cell showed only a slight increase in ESR (20%) and a negligible decrease in capacitance (5%).
[0147] Table 4 highlights the EDLC performance advantage of AC-CNT cells using this binary electrolyte operating at 3 V. A 25 percent increase in volumetric capacitance and energy density is achieved with the combined system.
[0148] Table 4
[0149]
[0150] Example 5 - Using a high sp 2 Carbon content in the bottom layer reduces the ESR of EDLC batteries
[0151] When the AC-CNT active layer was deposited onto a current collector with a conductive carbon primer layer, the adhesion of the AC-CNT active layer to the underlying current collector foil was improved compared to when the AC-CNT active layer was deposited onto an uncoated current collector foil. Furthermore, when electrodes including an AC-CNT active layer deposited on a carbon-primed current collector foil were assembled into EDLC pouch cells and the performance was evaluated, the chemical properties of the carbon underlayer had a significant effect on the EDLC cell ESR. Fig.16 The Nyquist impedance characteristics of cells containing AC-CNT active layers fabricated on three types of Al current collector foils with either PC-based or ACN-based electrolytes are shown. One foil type is uncoated and the other two are coated with carbon underlayers of different carbon (C) hybridization states. The current collector foil with underlayer 1 contains >50% C in sp 2 hybrid state, while the foil with bottom layer 2 contains > 65% C in sp 3 Hybrid state. With 2 (more sp 3 The Nyquist characteristic curve of the battery with AC-CNT electrodes fabricated on hybrid C) shows an undesirable semicircle at high frequencies. 2 For cells with AC-CNT electrodes fabricated on PC (with a high C content), such artifacts are clearly absent in the Nyquist characteristic curve. 2 The combination of carbon bottom layer 1 showed the lowest battery ESR value (<1Ω·cm 2 ).
[0152] Table 5 summarizes the ESR values of EDLC cells with AC-CNT electrodes fabricated on current collectors without or with different underlayers.
[0153] Table 5
[0154]
[0155] Example 6 - Reduction of ESR of EDLC Cells Using AC-CNT Electrodes with Carbon Black (CB)
[0156] Table 6 summarizes the EDLC performance comparison between cells with AC-CNT 80:20wt% electrodes and AC-CNT 80:15wt% electrodes containing 5wt% carbon black. For EDLC cells assembled with PC-based electrolytes, the inclusion of carbon black in the electrode composition reduced the ESR by about 4% compared to cells with AC-CNT electrodes. In the case of AC-CNT-CB electrodes, a larger reduction in cell ESR of about 7% was observed in an ACN-based electrolyte. However, the reduction in cell ESR in the case of AC-CNT-CB electrodes was accompanied by a concomitant reduction in volumetric capacitance compared to AC-CNT cells. Therefore, by replacing a small portion of CNTs with CB, higher power density can be achieved at the expense of lower energy density.
[0157] Table 6
[0158]
[0159] From the foregoing it will be appreciated that specific embodiments of the invention have been described herein for purposes of illustration, but that various modifications may be made without deviating from the spirit and scope of the invention.
Claims
1. A supercapacitor cell having at least one electrode, the at least one electrode comprising a current collector, an active layer, and a bottom layer between the current collector and the active layer, wherein the active layer comprises activated carbon and carbon nanotubes having a purity of at least 98 wt% and is free of a binder, wherein the content of carbon nanotubes in the active layer is between 15 and 25 wt%, wherein the bottom layer comprises a carbon layer, at least 40% of the carbon in the carbon layer is in the sp 2 hybrid state, and the bottom layer does not include carbon in the form of CNTs.
2. The supercapacitor cell of claim 1, wherein the activated carbon has a BET surface area of at least 1,000 m 2 / g, and the BET surface area of the carbon nanotubes is at least 400m 2 / g.
3. The supercapacitor cell of claim 1, wherein the carbon nanotubes are single-walled carbon nanotubes.
4. The supercapacitor cell of claim 3, wherein the carbon nanotubes have a length of at least 1 μm. 5 . The supercapacitor cell according to claim 3 , wherein the carbon nanotube has a Raman G / D integrated peak area ratio of at least 20 measured using a laser having a wavelength of 532 nm.
6. The supercapacitor cell of claim 1, wherein the electrode does not include carbon black.
7. The supercapacitor cell of claim 1, wherein the thickness of the active layer is between 30 μm and 200 μm.
8. The supercapacitor cell of claim 1, further comprising a second electrode, wherein a volume ratio of the two electrodes is between 1 and 1.
25.
9. The supercapacitor cell of claim 1, wherein the current collector comprises aluminum.
10. The supercapacitor cell of claim 1, further comprising a second electrode, a separator positioned between the two electrodes, and a conductive solution comprising an electrolyte, wherein the electrolyte comprises acetonitrile, propionitrile, propylene carbonate, or any combination thereof.
11. The supercapacitor cell of claim 1 , further comprising a second electrode, a separator positioned between the two electrodes, and a conductive solution comprising an electrolyte, wherein the electrolyte comprises triethyl-methyl-ammonium tetrafluoroborate (TEMA-BF4) dissolved in at least 99.9% pure propylene carbonate, tetraethyl-ammonium tetrafluoroborate (TEA-BF4) dissolved in at least 99.9% pure acetonitrile, or tetraethyl-ammonium tetrafluoroborate (TEA-BF4) dissolved in at least 99.9% pure propionitrile.
12. A supercapacitor battery having at least one electrode, the at least one electrode comprising a current collector and an active layer, wherein the active layer comprises activated carbon and carbon nanotubes having a purity of at least 98 wt % and is free of a binder, wherein the electrode further comprises carbon black, wherein the supercapacitor further comprises a bottom layer between the current collector and the active layer, wherein the bottom layer comprises a carbon layer, at least 40% of the carbon in the carbon layer is in the sp 2 hybrid state, and the bottom layer does not include carbon in the form of CNTs.
13. The supercapacitor cell of claim 12, wherein the amount of carbon black is greater than 1 wt% but less than 6 wt%.
14. A supercapacitor battery having at least one electrode, the at least one electrode comprising a current collector and an active layer, wherein the active layer comprises activated carbon and carbon nanotubes having a purity of at least 98 wt % and is free of a binder, wherein the supercapacitor battery further comprises a bottom layer between the current collector and the active layer, wherein the bottom layer comprises a carbon layer, at least 40% of the carbon in the carbon layer is in the sp 2 hybrid state, and the bottom layer does not include carbon in the form of CNTs.
15. The supercapacitor cell of claim 14, wherein the bottom layer has a thickness between 0.01 and 10 μm.
16. The supercapacitor cell of claim 14, wherein the content of carbon nanotubes in the active layer is between 10 and 30 wt%.
17. The supercapacitor cell of claim 16, wherein the content of carbon nanotubes in the active layer is between 15 and 25 wt%.
18. The supercapacitor cell of claim 14, wherein the activated carbon has a BET surface area of at least 1,000 m 2 / g, and the BET surface area of the carbon nanotubes is at least 400m 2 / g.
19. The supercapacitor cell of claim 14, wherein the carbon nanotubes are single-walled carbon nanotubes.
20. The supercapacitor cell of claim 19, wherein the carbon nanotubes have a length of at least 1 μm. 21 . The supercapacitor cell of claim 19 , wherein the carbon nanotubes have a Raman G / D integrated peak area ratio of at least 20 measured using a laser having a wavelength of 532 nm.
22. The ultracapacitor cell of claim 14, wherein the electrode does not include carbon black.
23. The supercapacitor cell of claim 14, wherein the active layer has a thickness between 30 μm and 200 μm.
24. The supercapacitor cell of claim 14, further comprising a second electrode, wherein a volume ratio of the two electrodes is between 1 and 1.
25.
25. The ultracapacitor cell of claim 14, wherein the current collector comprises aluminum.
26. The supercapacitor cell of claim 14, further comprising a second electrode, a separator positioned between the two electrodes, and a conductive solution comprising an electrolyte, wherein the electrolyte comprises acetonitrile, propionitrile, propylene carbonate, or any combination thereof.
27. The supercapacitor cell of claim 14, further comprising a second electrode, a separator positioned between the two electrodes, and a conductive solution comprising an electrolyte, wherein the electrolyte comprises triethyl-methyl-ammonium tetrafluoroborate (TEMA-BF4) dissolved in at least 99.9% pure propylene carbonate, tetraethyl-ammonium tetrafluoroborate (TEA-BF4) dissolved in at least 99.9% pure acetonitrile, or tetraethyl-ammonium tetrafluoroborate (TEA-BF4) dissolved in at least 99.9% pure propionitrile.
28. A supercapacitor battery having at least one electrode, the at least one electrode comprising a current collector and an active layer, wherein the active layer comprises activated carbon and carbon nanotubes having a purity of at least 98 wt % and is free of a binder, wherein the supercapacitor battery further comprises a bottom layer between the current collector and the active layer, wherein the bottom layer comprises a carbon layer, at least 40% of the carbon in the carbon layer is in the sp 2 hybrid state, and the bottom layer does not include carbon in the form of CNTs, wherein the supercapacitor cell further includes a second electrode, a separator positioned between the two electrodes, and a conductive solution including an electrolyte, wherein the electrolyte includes propylene carbonate, dimethyl carbonate, and 5-azaspiro-[4,4]-nonane-tetrafluoroborate.